THE CORRELATION LEVEL OF KNOWLEDGE OF DENTAL NURSING STUDENTS' ANXIETY REGARDING THE HAZARDS OF RADIATION IN PANORAMIC EXAMINATION AND DENTAL RADIOGRAPHY - Prayoga, Aryadiva Nugrahaning (Journal of Applied Health Management and Technology, 2023)
Knowledge is information that has been combined with understanding and the potential to act; which then sticks in someone's mind. Anxiety is an unreal fear, a feeling of being threatened in response to something that is not actually threatening, according to psychodynamic theory anxiety arises when self-will demands detachment from the ego. Panoramic radiography is a supporting tool that can be used to diagnose a case, such as the presence of a jaw fracture, symmetrical or asymmetrical evaluation of the TMJ or knowing the depth of caries.In radiological examinations, especially dental and panoramic, there are many worries or fears that arise when an examination is carried out. So it is necessary to increase knowledge in order to reduce the anxiety that arises.This type of research used is descriptive correlational research. The population and sample in this study were Diploma III students at the Department of Dental Nursing, Poltekkes Semarang who coincidentally (accidentally) met with researchers who were considered suitable with the specified sample characteristics to be sampled.The results of the Spearman rank test on the relationship between the level of knowledge and the anxiety level of the respondents obtained the Spearman rank correlation value (Rs) of -0.600, meaning that the higher the patient's level of knowledge about panoramic and dental radiographic examinations, the lower the patient's anxiety level. All respondents had no anxiety when dealing with radiological examinations, especially dental and panoramic examinations.